Pelaksanaan UU No. 24 Tahun 2009 pasal 36 ayat (3) - Bugar, Alwi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study describes the implementation of Law Number 24 of 2009 Article 36 paragraph (3) regarding the use of Indonesian in business names and the use of foreign languages in the names of shops, buildings, offices, trading complexes, business institutions, in the city of Padangsidimpuan. This study uses a behaviorist approach to determine the extent to which shop owners, buildings or buildings, offices, complexes in the city of Padangsidimpuan use Indonesian language for shops, buildings or buildings, office premises, trade complexes, places of business, made by Indonesian citizens in the city of Padangsidimpuan. The author uses secondary data to see the perpetrator/store owner write it down as a name. The study analyzed in this study is the use of the Indonesian language which applies to the laws and regulations of Law Number 24 of 2009 Article 36 paragraph (3). Research shows that many business entities do not use Indonesian in using the names of their shops/buildings. However, this finding shows that the use of Indonesian for shop owners, buildings or buildings, roads, apartments or settlements, offices, trade complexes, trademarks, business institutions, educational institutions, organizations founded by Indonesian citizens in the city of Padangsidimpuan shows a contradictory attitude. with the policy in Law no. 24 of 2009 Article 36 paragraph (3)